Event Study: Pengumuman Laba Terhadap Reaksi Pasar Modal (Study Empiris, Bursa Efek Indonesia 2004-2006) - Binsar I. K. Telaumbanua; Sumiyana Sumiyana (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2008)
This paper examines the investor reaction to earnings announcement around publication dates. This paper divides into two categories. There are the positiveearning announcements which include EPS increasing, and the negative-earning announcements which consist EPS decreasing. The examination of content and efficient market hypothesis used event study. We propose one hypothesis as positifearnings announcement and negative-earnings announcement correlate to stock price reactions in IDX. The sample are the 29 companies from LQ 45 that release the annual earnings of year 2004-2006. The earnings announcement date is taken from Indonesian Securities Supervisory Agency (Bapepam). Statistical test with standard error of estimate (SEE) was used to test the abnormal return during event periods. The results show that investor do not respond significantly to the positive and negative earnings announcement at the announcement dates. In addition, earning announcements suggest information contents to capital market. Finally, the empirical result is contrary to the finding of Ball and Brown (1968), Foster (1977), and Hayn (1995). However, this evidence supports the Lako’s studies (2002a, 2002c).